2019
DOI: 10.2174/1566524019666190627122655
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interleukin 38 on Inflammation-induced Corneal Neovascularization

Abstract: Background: Angiogenesis is tightly linked to inflammation. Cytokines of interleukin 1 (IL-1) family are key mediators in modulating inflammatory responses. Methods: In this study, we examined the role of IL-38, a member of the IL-1 family, in mediating inflammation-induced angiogenesis. Results: The results showed that the angiogenesis was attenuated by topical administration of IL-38 to the injured corneas in a mouse model of alkali-induced corneal neovascularization (CNV). Further study showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…IL‐38 can inhibit endothelial cell proliferation and migration via reducing the expression of angiogenic factors. Also, IL‐38 can decrease the expression of IL‐8 and TNF‐α to limit the activation of angiogenesis 34–38 . Wei et al 39 showed that IL‐38 inhibited the inflammatory response in the infarcted heart, and inflammatory cardiomyocytes inhibited apoptosis and alleviated ventricular remodeling through the release of IL‐38 40 .…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐38 can inhibit endothelial cell proliferation and migration via reducing the expression of angiogenic factors. Also, IL‐38 can decrease the expression of IL‐8 and TNF‐α to limit the activation of angiogenesis 34–38 . Wei et al 39 showed that IL‐38 inhibited the inflammatory response in the infarcted heart, and inflammatory cardiomyocytes inhibited apoptosis and alleviated ventricular remodeling through the release of IL‐38 40 .…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…Also, IL‐38 can decrease the expression of IL‐8 and TNF‐α to limit the activation of angiogenesis. 34 , 35 , 36 , 37 , 38 Wei et al 39 showed that IL‐38 inhibited the inflammatory response in the infarcted heart, and inflammatory cardiomyocytes inhibited apoptosis and alleviated ventricular remodeling through the release of IL‐38. 40 Although reperfusion therapy was an effective method to address coronary occlusion, excessive myocardial ischemia‐reperfusion injury remains existed.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…The polarization of macrophages to M1 type will release inflammatory factors such as IL-6, TNF-α, and IL-1. Among these pro-angiogenic molecules, IL-6 is a pro-inflammatory cytokine produced in corneal chemical burn tissue, which is known to induce the production of angiogenic factors to promote CNV [ 11 , 13 , 36 ]. TNF-α, which is mainly synthesized by macrophages, also plays a key role in inflammatory diseases, increasing the expression of adhesion molecules and inflammatory mediators in human corneal epithelial cells, and recruiting leukocytes by producing chemokines [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been interrogated that if IL-38 is topically administrated in the injured cornea of the mentioned model, inflammation-induced angiogenesis is diminished. IL-38 is capable of attenuating thee secretion of IL-1β, IL-6, IL-8, and TNF-α cytokines and reducing angiogenesis-related activities (e.g., proliferation, migration, and tube formation of human retinal endothelial cells) [153].…”
Section: Role Of Il-38 In Inflammatory Disorders Inflammation-induced Corneal Neovascularizationmentioning
confidence: 99%